Mitochondrial Translocator Protein (TSPO) Expression in the Brain After Whole Body Gamma Irradiation - Betlazar, Calina; Middleton, Ryan J.; Howell, Nicholas; Storer, Ben; Davis, Emma; Davies, Justin; Banati, Richard; Liu, Guo-Jun (Frontiers in Cell and Developmental Biology, 2021)
The brain’s early response to low dose ionising radiation, as may be encountered during diagnostic procedures and space exploration, is not yet fully characterised. In the brain parenchyma, the mitochondrial translocator protein (TSPO) is constitutively expressed at low levels by endothelial cells, and can therefore be used to assess the integrity of the brain’s vasculature. At the same time, the inducible expression of TSPO in activated microglia, the brain’s in-trinsic immune cells, is a regularly observed early indicator of subtle or incipient brain pathology. Here, we explored the use of TSPO as a biomarker of brain tissue injury following whole body irradiation. Post-radiation responses were measured in C57BL/6 wild type (Tspo+/+) and TSPO knockout (Tspo-/-) mice 48 h after single whole body gamma irra-diations with low doses 0 Gy, 0.01 Gy and 0.1 Gy and a high dose of 2 Gy. Additionally, post-radiation responses of primary microglial cell cultures were measured at 1, 4, 24 and 48 h at an irradiation dose range of 0 Gy-2 Gy. TSPO mRNA and protein expression in the brain showed a decreased trend after 0.01 Gy relative to sham-irradiated con-trols, but remained unchanged after higher doses. Immunohistochemistry confirmed subtle decreases in TSPO ex-pression after 0.01 Gy in vascular endothelial cells of the hippocampal region and in ependymal cells, with no de-tectable changes following higher doses. Cytokine concentrations in plasma after whole body irradiation showed differential changes in IL-6 and IL-10 with some variations between Tspo-/- and Tspo+/+ animals. The in vitro meas-urements of TSPO in primary microglial cell cultures showed a significant reduction 1 hour after low dose irradiation (0.01 Gy). In summary, acute low and high doses of gamma irradiation up to 2 Gy reduced TSPO expression in the brain’s vascular compartment without de novo induction of TSPO expression in parenchymal microglia, while TSPO expression in directly irradiated, isolated, and thus highly activated microglia, too, was reduced after low dose ir-radiation. The potential link between TSPO, its role in mitochondrial energy metabolism and the selective radiation sensitivity, notably of cells with constitutive TSPO expression such as vascular endothelial cells, merits further ex-ploration.